THE INFLUENCE OF SUSTAINABILITY REPORT AND FINANCIAL PERFORMANCE ON THE PROFITABILITY OF SHARIA BANKING COMPANIES REGISTERED IN INDONESIA AND MALAYSIA, 2021-2023 - Sri Mulyati; Yuli Agisna; Panji Agnyoto (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This research aims to examine the influence of sustainability reports and financial performance on profitability. The population in this study consists of banking sector companies registered in Indonesia and Malaysia in 2021-2023. This research uses multiple regression analysis using the EVIEWS 12 program using quantitative descriptive methods, namely by describing data and facts from the results of Sustainability Report calculations using the Sustainability Report Disclosure Index (SRDI), Financial Performance using ROE and Profitability. measured using Return On Assets (ROA). The research results show that the independent variable Sustainability Report (SR) has no effect on the dependent variable Profitability, but Financial Performance has an effect on the dependent variable profitability.